Writing the Digital History of Nazi Germany : Potentialities and Challenges of Digitally Researching and Presenting the History of the Third Reich, World War II, and the Holocaust - Julia Timpe; Frederike Buda (De Gruyter, 2022)
How do scholarship and practices of remembrance regarding Nazi Germany benefit from digital tools and approaches? What challenges arise from'doing history digitally'in this field – and how should they best be dealt with? The eight chapters of this book explore these and related questions. They discuss the digital initiatives of various archives and source databases, highlight　findings of research undertaken with digital tools, and examine how such tools can be used to present history in education, exhibitions and memorials. All contributions focus on recent or, in some cases, ongoing digital projects related to the history of National Socialism, World War II, and the Holocaust.